Labor competencies and labor demand of Economic Engineering graduates, UNI 2017 - Saavedra Pacheco, José (2017)
The present study on the relationship between the labor competencies of the graduates of the Professional School of Economic Engineering and the demand of the companies, analyzes quantitatively the process of labor insertion of the university graduates of this school connected to the requirements that the private or public companies in metropolitan Lima request in the practice of the professional practice of the economist. This study shows the sensitivity and importance that the EPIEC_ UNI should place on the employment training of its graduates. The research work is divided into 4 chapters: Chapter 1 refers to the problem statement in two aspects: The foundation of the problem, in which it is determined that there is a divorce between what the professional school of economic engineering provides and what employers demand. Secondly, the research question is posed: What are the labor competencies that the graduates of the professional school of economic engineering. UNI must acquire in order to successfully enter the labor market in metropolitan Lima? Chapter 2, theoretical framework, highlights the concept of labor competencies, understood as the skills required by graduates to successfully face the different areas of business activities in the macroeconomic, microeconomic, marketing and investment projects fields.  Chapter 3 presents the hypotheses of the study. The main hypothesis: If the graduates of economic engineering at UNI acquire labor competencies that the labor market demands, they would be more successful in the labor market. The secondary hypotheses are presented. Chapter 4 presents the methodology and the development of the research: The opinion of the graduates of the last four academic cycles through surveys and on the other hand the selection of 20 companies, private and public sector, to collect the version of the employer regarding the capabilities of the graduates of the EPIEC- UNI. Chapter 5 presents the main conclusions and finds a significant relationship between the labor competencies of EPIEC-UNI graduates and labor demand.